2015
DOI: 10.1002/2014jd022812
|View full text |Cite
|
Sign up to set email alerts
|

Traffic‐related air quality trends in São Paulo, Brazil

Abstract: The urban population of South America has grown at 1.05%/yr, greater urbanization increasing problems related to air pollution. In most large cities in South America, there has been no continuous long-term measurement of regulated pollutants. One exception is São Paulo, Brazil, where an air quality monitoring network has been in place since the 1970s. In this paper, we used an air quality-based approach to determine pollutant trends for emissions of carbon monoxide (CO), nitrogen oxides (NO x ), ozone (O 3 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 50 publications
1
25
0
7
Order By: Relevance
“…Fato semelhante já foi observado em um estudo realizado em Curitiba, estado do Paraná, onde verificou-se que um aumento de 65% no número de veículos não resultou no aumento da concentração dos poluentes atmosféricos, devido a vários fatores relacionados ao PROCONVE (ESCUCIATTO et al, 2016). Em relação ao O 3 , esse gás parece não possuir tendência de aumento ou diminuição clara ao longo do tempo, o que implica na sugestão de que, provavelmente, a formação de O 3 não é diretamente proporcional ao consumo de combustível (PÉREZ-MARTÍNEZ et al, 2015). O O 3 é um poluente secundário, sintetizado de forma não linear a partir de óxidos de nitrogênio (NOx) e dependente da radiação RBCIAMB | n.47 | mar 2018 | 61-73 ultravioleta, da hora do dia, dos parâmetros meteorológicos e da topografia (SEIGNEUR et al, 2003;PÉREZ-MARTÍNEZ et al, 2015).…”
Section: Complementando a Iniciativa Em 2002 Foi Instituído O Progrunclassified
See 2 more Smart Citations
“…Fato semelhante já foi observado em um estudo realizado em Curitiba, estado do Paraná, onde verificou-se que um aumento de 65% no número de veículos não resultou no aumento da concentração dos poluentes atmosféricos, devido a vários fatores relacionados ao PROCONVE (ESCUCIATTO et al, 2016). Em relação ao O 3 , esse gás parece não possuir tendência de aumento ou diminuição clara ao longo do tempo, o que implica na sugestão de que, provavelmente, a formação de O 3 não é diretamente proporcional ao consumo de combustível (PÉREZ-MARTÍNEZ et al, 2015). O O 3 é um poluente secundário, sintetizado de forma não linear a partir de óxidos de nitrogênio (NOx) e dependente da radiação RBCIAMB | n.47 | mar 2018 | 61-73 ultravioleta, da hora do dia, dos parâmetros meteorológicos e da topografia (SEIGNEUR et al, 2003;PÉREZ-MARTÍNEZ et al, 2015).…”
Section: Complementando a Iniciativa Em 2002 Foi Instituído O Progrunclassified
“…Em relação ao O 3 , esse gás parece não possuir tendência de aumento ou diminuição clara ao longo do tempo, o que implica na sugestão de que, provavelmente, a formação de O 3 não é diretamente proporcional ao consumo de combustível (PÉREZ-MARTÍNEZ et al, 2015). O O 3 é um poluente secundário, sintetizado de forma não linear a partir de óxidos de nitrogênio (NOx) e dependente da radiação RBCIAMB | n.47 | mar 2018 | 61-73 ultravioleta, da hora do dia, dos parâmetros meteorológicos e da topografia (SEIGNEUR et al, 2003;PÉREZ-MARTÍNEZ et al, 2015). Por isso, é complexo predizer como será seu comportamento a partir da emissão dos poluentes primários, no entanto, é fato que sua concentração aumenta no verão, o que ocorre inversamente aos demais poluentes estudados.…”
Section: Complementando a Iniciativa Em 2002 Foi Instituído O Progrunclassified
See 1 more Smart Citation
“…It should be noted that, unlike other pollutants, for which hourly pollutant concentrations have been recorded (by CETESB) since 1996, PM 2.5 has been monitored only since 2005. Carvalho et al (2015) and Perez-Martinez et al (2015) showed the impact of implementing programs for controlling the vehicular emissions, establishing emissions factors more restricted and in accordance with international standards. Two programs-PROCONVE and PROMOT-imposed emission factors for each category of vehicle, including LDVs, HDVs and motorcycles.…”
Section: Programa De Controle Da Poluição Do Ar Por Veículos Automotomentioning
confidence: 99%
“…In 1990, the air quality standards were revised to include the concept of primary and secondary standards. Perez-Martinez et al (2015) and Carvalho et al (2015) performed a detailed analysis of the temporal variation of the regulated pollutants due to the changes in fuels, engines and air quality standards.…”
Section: Programa De Controle Da Poluição Do Ar Por Veículos Automotomentioning
confidence: 99%